Efektivitas komisi pemberantasan korupsi pasca revisi undang-undang: analisis penurunan independensi dan dampaknya terhadap pemberantasan korupsi - Al Avissena, Rausan Nur (Maliki Interdisciplinary Journal, 2026)
Corruption remains a significant challenge within Indonesia’s governmental system as it affects state financial losses, decreases public trust, and hinders national development. This study aims to analiyze the impact of the revision of Law Number 19 of 2019 on the independence of the Corruption Eradication Commission (KPK) and its influence on the effectiveness of corruption eradication efforts. The research applies a qualitative approach through literature review and critical analysis of changes in KPK regulations. The findings indicate that the revision of the KPK Law has weakened the institution’s independence through the establishment of the Supervisory Board, the conversion of employees into State Civil Apparatus (ASN), and restrictions on wiretapping and search authorities. These conditions have reduced the effectiveness of law enforcement, weakened the courage to handle major corruption cases, and decreased public trust in the KPK. In addition, the weakening of the KPK has also affected the quality of governance and the implementation of good governance principles. Therefore, a comprehensive evaluation of the revised KPK Law is needed to strengthen the independence and effectiveness of the KPK in combating corruption in Indonesia.